2017
DOI: 10.1186/s12890-017-0391-9
|View full text |Cite
|
Sign up to set email alerts
|

Switch of noninvasive ventilation (NIV) to continuous positive airway pressure (CPAP) in patients with obesity hypoventilation syndrome: a pilot study

Abstract: BackgroundObesity is a major worldwide public health issue. The main respiratory complication stemming from obesity is obesity hypoventilation syndrome (OHS). Most of the OHS patients diagnosed during an exacerbation are treated with non invasive ventilation (NIV). Up to date, no prospective study has demonstrated in real life conditions the feasibility of a systematic protocoled switch of NIV to continuous positive airway pressure (CPAP), once stability is achieved.MethodsIn this prospective study, we include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
1
21
0
2
Order By: Relevance
“…Furthermore, BPAP set up and maintenance requires adjustment of more variables and is more expensive than CPAP. 17 However, patients with severe OSA requiring high pressures on CPAP empirically find BPAP a more physiological breathing pattern and, thus, easier to tolerate.…”
Section: Summary At a Glancementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, BPAP set up and maintenance requires adjustment of more variables and is more expensive than CPAP. 17 However, patients with severe OSA requiring high pressures on CPAP empirically find BPAP a more physiological breathing pattern and, thus, easier to tolerate.…”
Section: Summary At a Glancementioning
confidence: 99%
“…An alternative to CPAP therapy is bilevel positive airway pressure (BPAP); however, BPAP is frequently overlooked as it employs similar features to CPAP including a facial mask and positive pressures for ventilation. Furthermore, BPAP set up and maintenance requires adjustment of more variables and is more expensive than CPAP . However, patients with severe OSA requiring high pressures on CPAP empirically find BPAP a more physiological breathing pattern and, thus, easier to tolerate.…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study that probed the feasibility of switching 15 OHS patients from NIV to CPAP also reported positive results . However, the patients in that study only had mild OHS.…”
Section: Discussionmentioning
confidence: 98%
“…Once these patients achieve clinical stability with resolution of respiratory failure, consideration can be given to switching the patients from NIV to CPAP therapy. This has been shown to be safe with no detriment in the control of sleep‐disordered breathing (oximetry‐capnography), respiratory failure (arterial blood gases), subjective sleep quality (Pittsburgh sleep quality index), daytime hypersomnolence (Epworth sleepiness score) or health‐related quality of life (severe respiratory insufficiency questionnaire) in the short term …”
Section: Management Of Obesity‐related Respiratory Failurementioning
confidence: 99%
“…This has been shown to be safe with no detriment in the control of sleep-disordered breathing (oximetry-capnography), respiratory failure (arterial blood gases), subjective sleep quality (Pittsburgh sleep quality index), daytime hypersomnolence (Epworth sleepiness score) or health-related quality of life (severe respiratory insufficiency questionnaire) in the short term. 54 While much data exist that fail to demonstrate the clear superiority of NIV over CPAP therapy in patients with OHS and severe OSA, it must be appreciated that none were non-inferiority trials due to the powering and trial design. To illustrate this point, if the findings of the study by Howard et al are examined, although there is no difference in treatment failure between groups, the 95% CI provides an estimate of 13 fewer to 34 more patients per 100 achieving treatment success.…”
Section: Ohs With Significant Osamentioning
confidence: 99%